Reducing tax compliance costs through corporate tax base harmonisation in the European Union - Salvador Barrios; Diego d'Andria; Maria Gesualdo (European Commission, Joint Research Centre (JRC), 2019)
The reform proposal of the European Commission for a Common Consolidated Corporate Tax Base, the so-called CCCTB, is expected to significantly reduce the cost of doing business by lowering tax compliance costs for cross border operations within the European Union. However, to date the scarcity of comparable estimates on tax compliance costs has limited the assessment of such reduction. We exploit recently released and unique survey data designed to provide comparable information on corporate tax compliance costs in order to assess the impact of the CCCTB, using a general equilibrium modelling approach. Our results suggest that the reduction in tax compliance costs implied by the CCCTB would be associated with greater economic efficiency, including increases in both welfare and GDP. Member States resulting with the lowest compliance costs before the reform and having large inward foreign investment stock would benefit more from the CCCTB. Cross-border business operations would also benefit more from the CCCTB compared to domestic ones. The impact of the CCCTB on non-EU countries such as the US and Japan would be limited.
Keywords: H20; H30; C68; 330; CCCTB; tax compliance costs; European Union